Pengaruh Tingkat Inflasi,Tingkat Kurs Dan Produk Domestik Bruto Terhadap Ekspor Tekstil Dan Produk Tekstil Di Indonesia Tahun 2009-2024 - Carolina A. Roring; Tri Oldy Rotinsulu; George. M. V. Kawung (Jurnal Riset Multidisiplin Edukasi, 2025)
International trade has developed into a cooperative relationship between many countries because import and export transactions open up new jobs, encourage industrialization, transportation progress, and the presence of foreign businesses. Neither exporters nor importers affect international trade activities. This study aims to look at macroeconomic factors, namely the Inflation Rate, Exchange Rate and US Gross Domestic Product on Exports of Textile Commodities and Textile Products (TPT) in Indonesia both partially and simultaneously. This study is a quantitative study, the type of data used is secondary data in the form of time series data from 2009 - 2023 sourced from Bank Indonesia and the World Bank. The data collected is processed using the multiple linear regression analysis method with the help of Eviews version 12. The results of the study show that: (1) The Inflation Rate partially has a significant negative effect on TPT Exports in Indonesia. (2) The exchange rate partially has a positive and significant effect on TPT exports in Indonesia. (3) Gross Domestic Product partially has a negative and insignificant effect on TPT exports in Indonesia. (4) The inflation rate, exchange rate and Gross Domestic Product simultaneously have an effect on TPT exports in Indonesia.